Complementary Feeding and Growth Among Low Birthweight Infants in the The Second Half of Infancy: Results From a Multi-Site Observational Cohort. (14th June 2022) - Vesel, Linda; Duggan, Christopher; Koppad, Bhavna; Manji, Karim; Miller, Kate; Mvalo, Tisungane; Phiri, Melda; Saidi, Friday; Shamanur, Latha; Siddhartha, E S; Sudfeld, Christopher
Abstract: Objectives: This study was designed to address the high prevalence of infant undernutrition among low birthweight (LBW,  < 2.5kg) infants in the second half of infancy, and the dearth of evidence on the optimal transition and provision of complementary feeding and growth of LBW infants. The objectives were to understand the complementary feeding profile and growth outcomes in the second half of infancy; and to assess the relationship between poor nutritional status at the time of transition to complementary feeding and poor growth outcomes at one year. Methods: The results presented in this abstract are part of the larger Low Birthweight Infant Feeding Exploration (LIFE) study conducted in India, Malawi and Tanzania. This was a formative, multi-site, observational cohort study that collected data on over 1100 moderately LBW infants throughout infancy. After the six month visit, mother-infant pairs were visited at nine and 12 months. Results: A total of 1114 infants and their mothers were enrolled in the observational study. More than 95% of infants were fed breast milk at six, nine and 12 months of age. At nine and 12 months respectively, 48% and 31% of infants were not achieving a minimum acceptable diet, highlighting gaps in dietary diversity. A lack of dietary diversity was exacerbated among infants born to younger, less educated and/or multiparous mothers. Proteins were more limited than any other food group; only 66% and 70% of infants were fed animal source foods at nine and 12 months, respectively. Prevalence of stunting (>30%) increased from six to 12 months while underweight (26%) and wasting (10%) remained consistent; regional differences were observed. Importantly, poor growth outcomes at six months were predictive of those at 12 months even when adjusted for key covariates (stunting RR = 2.84, p < 0.001; underweight RR = 6.41, p < 0.001; wasting RR = 4.89, p < 0.001). Conclusions: Given the gaps in the optimal quality of complementary feeding and predictive relationship between six and 12 month growth outcomes, efforts should be made to enhance the promotion of feeding counseling before and during the transition to complementary feeding and to address key barriers to the provision of a diverse diet. In addition, growth monitoring and proactive intervention at six months or earlier could serve to prevent poor outcomes at one year of life. Funding Sources: Bill & Melinda Gates Foundation.